Temporally Local Tactile Codes Can Be Stored in Working Memory - Bhattacharjee, Arindam; Schwarz, Cornelius (Frontiers in Human Neuroscience, 2022)
Tactile exploration often involves sequential touches interspersed with stimulus-free durations (e.g., the time during which the hand moves from one textured surface to the other). Whereas it is obvious that texture related perceptual variables, irrespective of the encoding strategy, must be stored in memory for comparison, it is rather unclear which of those variables are held in memory. On the one hand, there are two established variables - ‘intensity’ and ‘frequency’, which are ‘temporally global’ variables because of the long stimulus integration interval required to average the signal or derive spectral components, respectively; on the other hand, a recently established third contender is the ‘temporally local’ variable that codes for kinematic profiles of very short, suprathreshold events in the vibrotactile signal. Here, we present the first psychophysical evidence that temporally local variables can be stored in memory. To that end we asked participants to detected changes in pulsatile indentation stimuli at their fingertip with and without a gap of 1 s between stimulus presentations. The stimuli either contained global variables alone (change of pulse rate), or a mix of local and global variables (change of pulse shape). We found, firstly, that humans are much better in detecting a change in stimuli when local variables are available rather than global ones alone. Secondly, this observation persists even when there is a gap between the stimuli, implying local variables must be stored in memory. Thirdly, an exhaustive array of intensity definitions (amongst them the commonly considered variable ‘mean speed’) failed to explain participants’ performance in any consistent manner, which implies that perceptual decisions were not driven by intensity coding. Taken together, we conclude that humans perform pulsatile change detection utilizing local pulse shape, and to a lesser degree global pulse rate, and that both parameters can be stored in memory.